Kemampuan Daya Hambat Hand Sanitizer Eco-enzyme terhadap Pertumbuhan Bakteri E-Coli - Sorensen Febrian Putra (Institut Agama Islam Negeri Kerinci, 2023)
Eschericia coli bacteria are pathogenic microorganisms, one way to inhibit the growth of E. coli bacteria by using a hand sanitizer made by applying biotechnology in general can reduce the growth of bacteria on hands. Currently, there are many developments in the manufacture of hand sanitizers made from natural ingredients. Natural ingredients that can be used to make hand sanitizers are Eco-enzymes. The purpose of this study to determine the inhibitory ability of hand sanitizer from Eco-enzyme to the growth of E-coli bacteria. using the true experimental method with 4 comparisons of hand sanitizer eco-enzyme with 2 repetitions, namely 7; 3, 5 ; 5, 3 ; 7, and 1 ; 9 to determine the inhibitory ability of hand sanitizers from eco-enzymes in inhibiting the growth of E-coli bacteria. The data observed was a description of the size and nature of the inhibition zone formed near the paper disc that was dripped with hand sanitizer. The first experiment got results if the hand sanitizer was in a ratio of 7; 3 and 5;5 is very good because the inhibition zone formed is large but scattered. In the second experiment, the same results were obtained but the inhibition zone was small.